KorA protein of promiscuous plasmid RK2 controls a transcriptional switch between divergent operons for plasmid replication and conjugative transfer. - Jagura-Burdzy, G (1994)
The trfA and trb operons, encoding genes essential for replication and conjugative transfer of broad host range plasmid RK2, are transcribed divergently. Deletion analysis presented here indicates that trfAp and trbAp are arranged as face to face promoters. The presence of the korA gene, whose product is known to repress seven operons on RK2, including the trfA operon, is shown here to stimulate trbAp. The effect of korA on trbAp is mimicked by the trfAp-1 promoter down mutation, suggesting that a reduction in the activity of trfAp is required for derepression of trbAp activity. The trfAp-1 mutation reduces RNA polymerase binding and open complex formation at trfAp but does not stimulate melting at trbAp in vitro. Therefore, the inhibition of trbAp is most probably due to forward transcription initiated at trfAp. The simultaneous inhibition/stimulation by KorA is seen even in the presence of the other repressors KorB and TrbA, which act at this region, thus providing a dominant mode of coordinating plasmid replication and transfer. This may be one of the keys to understanding how the maintenance and spread of promiscuous plasmids are balanced in different environments.